2010
DOI: 10.1055/s-0030-1249908
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based Identification ofHelleborus nigerby High-Resolution Melting Analysis

Abstract: Hellbori nigri rhizoma is a drug that is difficult to distinguish from other species of the genus Helleborus. In this communication we present a DNA-based identification by high-resolution melting analysis (HRM) that is able to differentiate between Helleborus niger and other species of the genus. HRM is a very specific, time- and labour-saving method for identifying DNA sequence variations and is ideally suitable for routine PCR analysis. The HRM assay developed is specific for the genus Helleborus. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The first study reporting the use of Bar-HRM to study herbal medicine substitution has recently been reported in a study on species substitution among three medicinal species of Acanthaceae [84]. Bar-HRM has also been used in a number of comparable methodologies [85], such as for authentication of an EU Protected Designation of Origin product made from Lathyrus clymenum [86], olive oil and adulterants [87], subspecies cultivar identification in eggplant [88], identification of closely related species relevant to TDG [89,90], species distinction in Mediterranean pines [91], detection of allergenic hazelnut contamination [92], and processed bean crops [93][94][95].…”
Section: Bar-high Resolution Meltingmentioning
confidence: 99%
“…The first study reporting the use of Bar-HRM to study herbal medicine substitution has recently been reported in a study on species substitution among three medicinal species of Acanthaceae [84]. Bar-HRM has also been used in a number of comparable methodologies [85], such as for authentication of an EU Protected Designation of Origin product made from Lathyrus clymenum [86], olive oil and adulterants [87], subspecies cultivar identification in eggplant [88], identification of closely related species relevant to TDG [89,90], species distinction in Mediterranean pines [91], detection of allergenic hazelnut contamination [92], and processed bean crops [93][94][95].…”
Section: Bar-high Resolution Meltingmentioning
confidence: 99%
“…Assays using universal primers targeting the matK gene detected a level of 0.1 % contamination in an admixture of H. niger and an unknown species, but by using primers specific to the common adulterant Veratrum nigrum, the assay detected a level of 0.0005 % contamination of the H. niger/V. nigrum admixture [76].…”
Section: High-resolution Meltingmentioning
confidence: 96%
“…Perhaps surprisingly, HRM has only been applied sparingly to detect adulterants in botanicals. High-resolution melting was used to identify Helleborus niger L. by targeting chloroplast trnL-trnF and matK regions [76]. Although data are limited, assays using universal primers appear to be less sensitive in detecting adulterants than those that target specific adulterant taxa.…”
Section: High-resolution Meltingmentioning
confidence: 99%
“…The first study reporting the use of Bar-HRM to evaluate herbal medicine substitution came from a recent investigation of species substitution among three medicinal species of Acanthaceae [ 29 ]. Bar-HRM has also been used in a number of comparable applications [ 34 ], such as for authentication of an EU Protected Designation of Origin product made from Lathyrus clymenum [ 35 ], for the identification of olive oil and adulterants [ 36 ], for subspecies cultivar identification in eggplants [ 37 ], for the identification of closely related species of Sideritis and Helleborus [ 38 , 39 ], for species distinction in Mediterranean pines [ 40 ], for the detection of allergenic hazelnut contamination [ 41 ], and for the identification of processed bean crops [ 42 44 ].…”
Section: Introductionmentioning
confidence: 99%